Implementation of Entrepreneurship in the Field of Tourism in Youth GMIMLogos Bumi Kilu Permai - Kondoj, Telly Hetty Isje; Solang, Jeanlly Adrie; Y.Gumolili, Youdi; Takaendengan, Mita Erdianty; Sendow, Debi Christiany (Journal of Universal Community Empowerment Provision, 2024)
Tourism-based entrepreneurship training is a simple service among young people or the millennial generation because they are very quick to adapt and adapt to the current situation and developments in the modern era. However, in its implementation it requires high levels of innovation and creativity to obtain new and useful business opportunities that can be carried out both individually and in groups. Tourism is a science that develops according to the demands and development of human civilization as well as a touch of creativity in the process of arranging and managing tourist areas with all the supporting facilities and infrastructure. The service method is carried out descriptively, in which the service person describes the service by interviewing the potential of tourist attractions in Manado and its surroundings, interviews regarding the participant's attraction to the tourist objects mentioned and/or known and visited. On this basis, knowledge and insight regarding entrepreneurial efforts in the tourism sector is given, where the field of entrepreneurship in the tourism sector is a very good field and has the potential to be pursued by young people. The aim of this service is to encourage and motivate the creativity and innovation of the youth of the GMIM Logos Congregation to elaborate their personal potential and abilities along with insight into their tourism knowledge and technological capabilities. This service applies creativity in the tourism sector for them to design itinerary products both in the city of Manado, Minahasa and the surrounding areas. This motivation will continue to attract attention and be supported by both the youth themselves, the church and the wider community. In the future, we hope to become a product provider, especially for internal activities in the congregation and it is hoped that business expansion will occur by improving relations with the outside world.